Teaching Excellence in Higher Education - Gregory, Marshall; Gregory, Melissa Valiska; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2013)
Marshall Gregory argues that teachers at the university and high school levels can achieve teaching excellence by grounding their teaching in pedagogical theory that takes into account students' abilities and the ultimate goals of teaching: to develop students' capacities for thought, reflection, questioning, and engagement to their fullest extent.
Keywords: Education; Philosophy and social sciences; Teaching; Higher education; Education -- Philosophy; Education; Higher Education; Philosophy of Education; Teaching and Teacher Education; Educational Philosophy